Corrosion resistance of welded joints made by underwater wet welding - Maksimov, Sergey; Radzievskaya, Alla; Nyrkova, Liudmyla; Osadchuk, Switlana (Transfer of innovative technologies, 2021)
One of the reasons of coming out of order of metal structures, operating in water environment, including sea conditions, is the corrosion. Thus, for example, the corrosion wear of metal of the ship hull underwater part can reach from 0.3 up to 0.5 mm/year. The corrosion of welds is the ever more critical situation. The rate of their fracture exceeds the rate of the base metal corrosion and in some cases it may reach 1-3 mm/year [1, 2]. The great selective corrosion in the form of fissures along the welds (on both sides) was observed in heat-affected zone (HAZ) metal of slot, butt welds and welds for welding-on to the basic workpiece, i.e. up to 1 mm/year, in some cases a through corrosion fracture of the fusion line (formation of blowholes) was observed [1]. In the opinion of the work authors [2] the welds are subjected to fracture due to the occurrence of thermal electromotive force between the parts welded under conditions of high electric conductivity of the sea water (Seebeck effect). To repair the corroded welded joints of metal structures, operated under the water, a wet underwater welding is used. At the E.O.Paton Electric Welding Institute the specialized flux-cored wires have been developed, which are designed for welding low-carbon and low-alloyed steels, including those of a higher strength. In the latter case the electrode materials of an austenite type are used to provide resistance against cold crack formation in the HAZ [3]. The work was aimed at study of corrosion resistance of welded joints with ferrite and austenite deposited metal, made by the underwater wet welding, under the conditions, which simulate the service conditions in sea water.